Analysis Of The Protection Of Workers' Rights In The Indonesian Labor Law - Japar, Muhammad; Fauziah, Fauziah; Lubis, Efrida; Fadillah, Syarif; Hermanto, Hermanto; Patras, Yuyun Elizabeth (PALAR (Pakuan Law review), 2025)
ABSTRACTThis study analyzes the protection of workers' rights in the Indonesian Manpower Law, focusing on basic workers' rights, implementation challenges, and recommendations for improving effectiveness. The method used is normative juridical with qualitative data analysis. The study results indicate that although labor regulations are available, their implementation is still weak. Minimum wages are often unmet, especially in the informal sector, due to weak supervision and low worker awareness of their rights. Social security is hampered by low company compliance and administrative constraints, while occupational safety and health (K3) standards are poorly implemented, as seen from the high number of work accidents. The right to leave, rest time, and freedom of association are also often ignored, with union busting still rampant. This study recommends stricter supervision, increased worker literacy, and collaboration between the government, employers, and trade unions to improve the implementation of regulations. These steps are expected to enhance the protection of workers' rights, support their welfare, and encourage sustainable economic growth. Keywords : Protection, Workers' Rights, Employment Law.